The Effect of Meditation Training on Increasing Concentration in Indonesian Kempo Federation Athletes at Graha BSS Narmada - Syariofeddin, Elya Wibawa; Sukartidana, I Nyoman; Sanrijaya, Niqsanding (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Concentration is a vital aspect of martial arts such as Kempo, which requires quick responses, technical precision, and mental composure. Based on observations and interviews with coaches and athletes from the Indonesian Kempo Federation at Graha BSS, Narmada, a problem of low concentration levels was identified, which affects the athletes' performance and achievement. Therefore, this study was conducted to examine the effect of meditation training on improving athletes’concentration. The research employed a quantitative approach with a one-group pretest-posttest experimental design, without a comparison group. The population consisted of 30 athletes, with a sample of 20 athletes selected using purposive sampling based on specific criteria. Meditation sessions were conducted over a onemonth period, totaling 12 meetings with a frequency of three sessions per week. The instrument used was the Concentration Grid Test (CGT), a measurement tool proven to be valid and reliable. Data collection techniques included documentation and performance-based testing to assess concentration levels before and after the intervention. The data were processed through editing, coding, saving, tabulating, and cleaning, and then analyzed using parametric statistics, including normality tests (Kolmogorov-Smirnov and Shapiro-Wilk), a homogeneity test (Levene’s Test), and hypothesis testing using the paired samples t-test. The findings showed an increase in the average concentration score from 9.45 (pre-test) to 15.15 (posttest), with a mean difference of 5.7 points. The t-test resulted in a significance value of 0.001 (< 0.05), indicating a statistically significant difference, meaning meditation training had a positive effect on the athletes’ concentration. Therefore, it can be concluded that “Meditation training has a positive influence on improving the concentration of athletes in the Indonesian Kempo Federation at Graha BSS, Narmada.